THE USE OF WATERFALL MODEL IN APPLICATION DESIGN WEB-BASED MARYAM DEPARTMENT STORE - Indarti -; Dewi Laraswati; Adi Supriyatna (Universitas Islam Kuantan Singingi, 2021)
Maryam Department Store is a groceries sales business. Cause of high demand for groceries needed by consumers, it also needed to notes the report fast. In increasing the service and ease of transactions, so thats way the system design in selling at Maryam Department Store. The implementation of this information system is expected to be a solution in solving problems and progress at Maryam Department Store. The system design model used is prototyping. The result of this research is a programming application for Maryam Department Store based on Web